Pakistan : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2010)
The government of Pakistan completed its second full Poverty Reduction Strategy Paper (PRSP-II) in December 2008. PRSP-II builds on the first Poverty Reduction Strategy Paper (PRSP-I), which was adopted in December 2003, but is shaped by recent political and economic developments. Against this background, PRSP-II focuses on regaining macroeconomic stability and the growth momentum of 5-7 percent a year, while protecting the poor and vulnerable-objectives that are supported by the IMF's Stand-By Arrangement and the World Bank's proposed Poverty Reduction and Economic Support Operation.